Analysis Of Teachers Readiness In Implementing The Independent Curriculum In Elementary Schools - Puspitasari, Putri Eka; Utami, Ratnasari Diah (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Along with the implementation of the independent curriculum, teacher readiness in implementing the independent curriculum is something that is absolutely realized so that the expected goals can be achieved. No matter how good a curriculum is, if the teacher does not have the readiness and skills, then the curriculum cannot be realized properly. This shows that the curriculum and teachers have a very close relationship. This study aims to determine the readiness of elementary school teachers in implementing the independent curriculum. This research uses descriptive research type. The object of this research is teacher readiness in implementing the independent curriculum at Muhammadiyah 1 Ketelan Elementary School, Surakarta. Meanwhile, the subjects of this study were school principals and teachers as actors in implementing the independent curriculum. Data collection techniques in this study include interviews, observation, and documentation. Test the validity of the data in this study using method triangulation and theory triangulation. Data analysis techniques in this study used data reduction (data reduction), data display (data presentation), and conclusion drawing/verification (drawing conclusions. The results of this study indicate that overall the teacher is ready to implement the independent curriculum. Outline of the six indicators of teacher readiness have fulfilled four indicators.With the other two indicators teachers still feel they do not understand and still need training regarding the preparation of teaching modules and learning assessment in the independent curriculum